Hailstorm and Human Excreta: Navigating the Hazardous Landscapes in Low-Income Communities in Mangaung, South Africa - Mphambukeli, Thulisile N. (Frontiers in Sustainable Cities, 2020)
This policy brief argues that due to the failure of local municipalities, political instability and corruption, hazards act synergistically with unequal and complex power relationships to reproduce and disproportionately distribute hazardous landscapes, particularly in the low-income communities of South Africa. It argues that when municipal bureaucrats hide behind a façade of claiming to do something about hazards and the associated challenges they present for low-income communities, but in reality take no action, they reveal their ‘dangerous mindscapes’ which have devastating effects on low-income communities. This study adopted a qualitative research design, grounded on the descriptive phenomenological approach. The study covers the period between 2015 and 2019. Twenty-four (24) in-depth interviews were conducted in the greater Mangaung low-income communities.